2011
DOI: 10.1037/a0023637
|View full text |Cite
|
Sign up to set email alerts
|

Federal standards for community registration of juvenile sex offenders: An evaluation of risk prediction and future implications.

Abstract: The enactment of the Adam Walsh Child Protection and Safety Act in 2006 is an extension of current protective legislation aimed at establishing stricter sanctions for community-released sexual offenders. What largely separates the Adam Walsh Act from previous registration and notification laws is the crossing of traditional jurisdictional boundaries between adult and juvenile courts at the federal level. This article addresses several key concerns relating to the application of these federal standards to adole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 55 publications
2
19
0
Order By: Relevance
“…Juvenile sex offenders are significantly more likely to be rearrested for nonsexual crimes (Caldwell, 2002), which suggests that sexual offending may be just one form of antisocial behavior (Jacob, Kennedy, & Meyer, 1997). Moreover, juvenile sex offenders respond to the same treatments as other nonsexual delinquents, again suggesting that there are important underlying similarities between these two groups (Batastini et al, 2011; also see Borduin, Schaeffer, & Heiblum, 2009).…”
Section: Predictors Of Juvenile Sex Offenders Not Distinctmentioning
confidence: 92%
See 2 more Smart Citations
“…Juvenile sex offenders are significantly more likely to be rearrested for nonsexual crimes (Caldwell, 2002), which suggests that sexual offending may be just one form of antisocial behavior (Jacob, Kennedy, & Meyer, 1997). Moreover, juvenile sex offenders respond to the same treatments as other nonsexual delinquents, again suggesting that there are important underlying similarities between these two groups (Batastini et al, 2011; also see Borduin, Schaeffer, & Heiblum, 2009).…”
Section: Predictors Of Juvenile Sex Offenders Not Distinctmentioning
confidence: 92%
“…Moreover, treatment for juvenile sexual offenders has been found to be effective and to lower the already low recidivism rate for juvenile offenders (Batastini, Hunt, Present-Koller, & DeMatteo, 2011). An evaluation of a specialized community-based treatment program, for example, found that assessment and treatment produced a 72% reduction in sexual recidivism on an average follow-up period of six years for adolescents completing at least 12 months of treatment (Worling & Curwen, 2000).…”
Section: Juvenile Sex Offenders Not Distinctly High Riskmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past, the inclusion of adolescent offenders was left to the discretion of states. However, SORNA mandates that adolescent offenders who are 14 years of age or older at the time of offense and who commit a specific type of crime (i.e., comparable to or more severe than aggravated sexual assault against a person younger than age 12) are subject to registration for up to 25 years to life (see Batastini, Hunt, Present-Koller, & DeMatteo, 2011, for a comprehensive review of the legislation). This dramatic shift in the law mandating the registration of juvenile offenders neglects the extant research emphasizing the differences in cognitive, social, and neurological development of youth compared with adults (Letourneau, Bandyopadhyay, Sinha, & Armstrong, 2009), and it conflicts with knowledge of the heterogeneity among juveniles who have sexually offended (Andrade, Vincent, & Saleh, 2006;Caldwell, 2007).…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Other researchers have demonstrated that federal standards for juvenile sex offender registration fail to distinguish between youth who will reoffend or not (Batastini, Hunt, Present-Koller, & DeMatteo, 2011;Caldwell, Ziemke, & Vittacco, 2008) as do state-specific methods in New Jersey, Texas, and Wisconsin (Caldwell & Dickinson, 2009;Caldwell et al, 2008). The basis for these federal and state policy failures might lie, in part, with the low sexual recidivism rate of youth adjudicated for sex offenses (Caldwell, 2002;Vandiver, 2006).…”
Section: Policy Recommendationsmentioning
confidence: 99%